2017
DOI: 10.1111/cdev.12755
|View full text |Cite
|
Sign up to set email alerts
|

A Small‐Scale Randomized Efficacy Trial of the Identity Project: Promoting Adolescents’ Ethnic–Racial Identity Exploration and Resolution

Abstract: Adolescents' ethnic-racial identity (ERI) formation represents an important developmental process that is associated with adjustment. The Identity Project intervention, grounded in developmental theory, was designed to engage adolescents in the ERI processes of exploration and resolution. The current small-scale efficacy trial involved an ethnic-racially diverse sample of adolescents (N = 215; M = 15.02, SD = .68) from eight classrooms that were randomly assigned by classroom to the intervention or attention c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
76
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 92 publications
(89 citation statements)
references
References 29 publications
(30 reference statements)
6
76
0
1
Order By: Relevance
“…One reason may be the short-term follow-up with only one post-test. A chain reaction from heritage identity exploration, to resolution, to global identity resolution may only show with a longer-term follow-up, such as across one year in the U.S. study (Umaña-Taylor, Douglass, Updegraff, & Marsiglia, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…One reason may be the short-term follow-up with only one post-test. A chain reaction from heritage identity exploration, to resolution, to global identity resolution may only show with a longer-term follow-up, such as across one year in the U.S. study (Umaña-Taylor, Douglass, Updegraff, & Marsiglia, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…As a practical implication, intercultural education in schools may help address cultural labels to enhance a mutual understanding for cultural differences (Stevick 2017), to prepare for participation in a culturally diverse world (Vedder and van Geel 2017), and to stimulate cultural socialisation with friends. Cultural identity interventions in school have shown that students who explored their identity have higher self-esteem and do better in school one year later (Umaña-Taylor et al 2017). Importantly, addressing cultural labels may illustrate the existing cultural heterogeneity and bring experiences of cultural inclusion or exclusion to the foreground of explaining educational disparities (Hüpping and Büker 2014).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the data also suggest that increasing ERI may lead to more positive developmental outcomes. Recent research finds that interventions focused on helping adolescents to explore the history, symbols, and traditions of their ethnic/racial group have resulted in higher levels of ERI (Umaña‐Taylor, Douglass, Updegraff, & Marsiglia, ).…”
Section: Discussionmentioning
confidence: 99%